AN ANALYSIS OF METAPHOR TRANSLATION IN HARPER LEE'S NOVEL ENTITLED TO KILL A MOCKING BIRD - Puji Priyanto, - (2011)
The aims of this research are to identify metaphors used in the novel, to find out the types of translation procedures used by translator to translate the metaphors and to describe the quality of translation of the metaphors in the novel. The data are collected from the novel in the form of textual evidences of the types of metaphors. The research was conducted by applying descriptive method with a qualitative approach. There are some stages in analyzing the data. The first was doing close reading both on the novel of English version and translated version. The second was by collecting and classifying the data into two types of metaphor as proposed by Larson (1984). The last was identifying the translation procedures based on Newmark's theory. Then, judging the quality of translation in terms of accuracy, clarity, and naturalness. The result of the research showed that there were two types of metaphor discovered in the novel. Those were 200 items of metaphors which consists of dead metaphors (76%) and live metaphors (24%). In translating dead metaphors, the translator used synonymy the most dominant procedure (67%), literal (22%), couplet (7%), addition (2%), transposition (1%), and modulation (1%). Meanwhile, in translating live metaphors, the translator employed synonymy the most frequently procedure (29%), literal (27%), couplet (23%), addition (15%), transposition (4%), and paraphrase (1%). Several procedures were applied by translator in translating metaphors. Synonymy was the most frequently applied procedure in translating metaphors (58%), literal (23%), couplet (10.5%), addition (5%), transposition (2%), modulation (1%), and the smallest one paraphrase (0.5%). The quality of the translation is generally acceptable, understandable and good (appropriate words, phrase and grammar and clear meaning) despite some translations which are unnatural. It can be concluded that dead metaphor was the most frequently found in the novel, and synonymy was the most frequently procedure employed in translating metaphor. In addition, metaphor are applied by the author is intended to give more aesthetic value and to deliver the author's intention of imaginative power.